Special Education in Sri Lanka: A snapshot of three provinces - Muttiah, Nimisha; Drager, Kathryn D.R.; O'Connor, Lindsay (Disability Studies Quarterly, 2016)
This study discusses special education services across three provinces of Sri Lanka. It sought to answer the following research questions: (a) who are the children receiving special education services? (b) what are the current special education practices? (c) what are parents' views on communication supports, inclusion and literacy? Sixty-seven parents from the Western, Southern and Northern provinces participated in an in-person survey interview. The results indicated no children older than 14 years and very few children with severe needs received school services. This study identified some key implications including a need for Speech and Language Therapists to work in schools. It also discusses the benefits and challenges of implementing inclusive education in low- and middle-income (LAMI) countries.